2021
DOI: 10.1039/d0tc04912c
|View full text |Cite
|
Sign up to set email alerts
|

Poly(n-vinylpyrrolidone-co-acrylonitrile-co-methacrylic acid)–graphene quantum dot conjugate: synthesis and characterization for sensing ammonia vapour

Abstract: We report the biosynthesis of Graphene QDs and their composite with poly(n-vinylpyrrolidone-co-acrylonitrile-co-methacrylic acid) for efficient detection of ammonia with a detection limit of 0.232 ppm using a fabricated portable electronic device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…By using the equation, 3.3σ/S, the LOD value was found to be 9 ppb, where σ and S are the relative standard deviation and slope of the calibration plot, respectively. 45 Although several HCl sensors based on various transduction mechanisms, including electrochemical, opto-chemical, optical, and colorimetry, 46−51 are reported in the literature, vapor-phase detection of HCl based on an AC impedance study was found to be the infrequent one among the others. Thus, PVA-supported NDI-10 film emerges as an advanced polymeric composite sensor based on AC impedance with a low LOD for HCl vapors.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the equation, 3.3σ/S, the LOD value was found to be 9 ppb, where σ and S are the relative standard deviation and slope of the calibration plot, respectively. 45 Although several HCl sensors based on various transduction mechanisms, including electrochemical, opto-chemical, optical, and colorimetry, 46−51 are reported in the literature, vapor-phase detection of HCl based on an AC impedance study was found to be the infrequent one among the others. Thus, PVA-supported NDI-10 film emerges as an advanced polymeric composite sensor based on AC impedance with a low LOD for HCl vapors.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In order to calculate the limit of detection (LOD), the calibration curve was plotted against different concentrations against the change in Z values (Figure S9). By using the equation, 3.3σ/ S , the LOD value was found to be 9 ppb, where σ and S are the relative standard deviation and slope of the calibration plot, respectively . Although several HCl sensors based on various transduction mechanisms, including electrochemical, opto-chemical, optical, and colorimetry, are reported in the literature, vapor-phase detection of HCl based on an AC impedance study was found to be the infrequent one among the others.…”
Section: Resultsmentioning
confidence: 99%
“…Not only pristine QDs, but also composite QDs have been used in sensing studies [76][77][78][79][80][81]. Graphene QDs (GQDs) is a 0D nanoscale carbon material, consisting of monoor a few layers of carbon atoms [82].…”
Section: Resistive-based Gas Sensors On Composite Qdsmentioning
confidence: 99%
“…This was believed for stable graphene dispersion with poly-N-vinyl-2-pyrrolidone (PNVP). Many reports are available on the fabrication or functionalization of graphene surfaces using NVP [37][38][39][40]. However, many of them include the preparation of graphene dispersions using graphene derivatives, such as graphene oxide and reduced graphene oxide [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports are available on the fabrication or functionalization of graphene surfaces using NVP [37][38][39][40]. However, many of them include the preparation of graphene dispersions using graphene derivatives, such as graphene oxide and reduced graphene oxide [39,40]. Only a few reports are available on the exfoliation of graphite [37,38], which consists of many steps, including the exfoliation of graphite, the preparation of polyvinyl pyrrolidone, and the preparation of graphene dispersions.…”
Section: Introductionmentioning
confidence: 99%